Business Model Canvas Application from A Peer-To-Peer Energy Transaction Service Provider Platform for Rooftop Solar Power Plant (PLTS) Customers - Zafya Nadhira Affiandi; Eko Adhi Setiawan (Budapest International Research and Critics University, 2022)
The electricity export-import scheme using rooftop solar PV by PLN customers, commonly known as net metering or net billing, was not attractive because it was only valued at 0, 65:1 for each price of electricity sold to the price of electricity in general. In mid-2021, the Ministry of Energy and Mineral Resources will revise the provisions on the export of electricity by valuing 1:1 for each electricity price sold. However, changing the export-import scheme can eliminate compensation for the cost of storing consumer electricity which PLN will bear in the future. At this time, the emergence of more proactive consumers with production and storage capabilities in the context of renewable energy, in other words,